النمذجة المكانية لاستثمار المياه الجوفية للزراعة في منطقة الشهابي - مسير لفته الزاملي . شاكر (Journal of College of Education, 2019)
Abstract Hydro chemical is considering of water imbricated science deal with chemical structure nater of water and double result between water uvality and reacties with earth surface formation ,container on mineral as wellas other factors such as surface water runoff temperature and runoff depth, and that fresh water industrial water that chemical and physical specifications are essential to determine the validity of water Analysis (10) samples were taken over the whole region in the rainy season to determine the chemical and physical properties and suitability for use and determine their suitability for agricultural uses in the area. It included the analysis of negative and positive ions as well as the determination of the hydrochemical formula for this water through the analysis of the study samples in the Wasit water directorate, and based on the classification of irrigation of the parameters according to the standard specifications were identified non-ideal (weak) and medium and ideal surface that can be invested for agriculture according to each element of groundwater elements in the study area